Corrosion Inhibition Study Of Carboxymethyl Celluloseionic Liquid Via Electrochemical And Machine Learning Technique - Adi Hafizamri Ariffin; Wan Mohd Norsani Wan Nik; Samsuri Abdullah; Mohd Ikmar Nizam Mohamad Isa; Vincent Izionworu; Mohammad Fakhratul Ridwan Zulkifli (PERSATUAN SAINS ANALISIS MALAYSIA, 2024)
Indexed by MyCite